Om den almene pædagogiks krise: Mellem ideologisk socialarbejde og psykologiseret læring. - Pio, Frederik (Studier i Pædagogisk Filosofi, 2020)
Abstract The article contains a discussion of the contemporary crisis of general education (Allgemeine Pädagogik) with special attention to: (i) how the cultural erosion and societal differentiation the last 40 years has downgraded the concepts of upbringing and education (Erziehung, Bildung) in favour of an increased attention towards concepts of socialization and learning. Secondly, the question of the relation between (ii) general education and the empirical-methodologically specified sub-disciplines is also raised, as these sub-disciplines are currently in the process of detaching themselves towards enhanced autonomy. Finally, the article looks into the difference between the research-programs respectively of general education and the social-psychological paradigm of educational research (Bildungsforschung, uddannelsesvidenskab). The total argument of the article claims, that the research program as well as educational program of general education is justified today by maintaining an approximate unity of a field of knowlegde currently under pressure towards a diffuse or even non-pedagogical nature. Therein lies the current inevitability of general education in our current po-mo societal formation.